Restriction endonuclease map of phage group 2 Staphylococcus aureus exfoliative toxin plasmid. - Warren, R L (1981)
A restriction endonuclease map of the phage group 2 Staphylococcus aureus exfoliative toxin plasmid pRW001 was constructed. The orientation of the restriction endonuclease fragments was determined by a series of single and double enzyme digestions. The location of the deletions found in pRW002, a naturally occurring deletion mutant of the exfoliative toxin plasmid, was determined by comparing the restriction endonuclease fingerprints of the two plasmids. This physical map provided a means for comparing other insertion or deletion mutants of the exfoliative toxin plasmid.